Does financial development hamper economic growth: empirical evidence from Bangladesh - Hye, Qazi Muhammad Adnan; Islam, Faridul (Journal of Business Economics and Management, 2013)
The objective of this study is twofold. (a) Construct the first ever financial development index (FDI) for Bangladesh using the principal component method (PCM). (b) Use the FDI to explore the existence of a long run relationship between FDI and economic growth. The Augmented Dickey Fuller and the Ng-Perron unit root tests have been applied to examine the stationarity properties of the series. To explore a long run relation, the Autoregressive Distributed Lag (ARDL) approach to cointegration; and to assess the stability of the parameters, the rolling window regression approach have been used. The results show that the impact of real interest rate (RIR) and FDI on economic growth is negative. Estimates from rolling window method show that FDI and RIR are negatively related to economic growth for the years 1987–1988, 1992–1999, 2002–2006, 2008 and 2009; and 1986–1998, 2006 and 2007, respectively. The results may help policymakers formulate effective financial sector policies as a tool to promote economic growth in Bangladesh. First published online: 12 Sep 2012